A kreol coastal confluence in Mahebourg, Mauritius - Auckloo, Rahul Raj (School of Architecture, Planning and Geomatics, 2024)
The personal interest of the author and Mauritian cultural dissolution concentre in this architectural research – in the cerebration of a Kreol Coastal Confluence. This design inquiry presents an architecture of mediation as key, which focalises the divergent spheres into the same space - artisanal fishing as the vernacular culture and the contemporary ‘development'. The architectural stance manifests as a re-imagination of an existing artisanal fish landing station in Mahebourg [debarcader]. The proposition is to demolish the current building footprint, retaining vertical structural elements where neccessary, crafting a scheme spatially more efficient and tailored for the existing process stages of artisanal fishing. To draw focus and enrichment into the localized fishing sphere and facilitate a contemporary growth of the community, the intersection of design and making spaces aim to extend the reach of practical, embodied skills and knowledge from the local cohort through to the younger generation. This frames a concentrated incentivised condition that has the capacity to rejuvenate the site's praxis and socio-spatial character. Proposed, is an architectural continuation of this [fishingdesign] intersection - the integration of the community's analogue practices of netting, boat building and processing, serve to influence the tectonic language and making of the building - seeking to prompt a sense of belonging between architecture and people. This architectural proposal is a system that operates between land and sea. The author seeks for a threshold, a new line between land and water amplifying the landscape with the ebb and flow of the ocean - inserting program amidst this change. This broadening of the threshold provides those on land with a smooth transition into the fishing waters, and provides those within, a phased and gradual disembarkment to land.